Dawson's fall - Robinson, Roxana (Sarah Crichton Books/Farrar, Straus and Giroux, 2019)
"The story of Dawson, his wife, Sarah, and their family during the violent days following the Civil War. Dawson is the editor in chief of a newspaper in Charleston, SC, trying to bring a dose of humanity and justice to a tumultuous world struggling to right itself"--